An uncommon presentation of Kikuchi Fujimoto disease: a case report with literature review - Ranabhat, Sabin (BMC Res Notes, 2015)
BACKGROUND: Kikuchi–Fujimoto disease is so named because Kikuchi and Fujimoto were the first scientists to describe it in Japan in 1972. Although the disease has been reported from all over the world and more so from Asia, it is rare. To date only eight cases have been reported from Nepal. Cervical lymphadenopathy, fever and raised Erythrocyte Sedimentation Rate are usual presenting features of this disease. We describe a case which presented with thrombocytopenia and axillary lymphadenopathy in addition to the usual features. Out of the total eight cases that have been reported from Nepal so far, no patients had thrombocytopenia and only one patient had axillary lymphadenopathy. CASE PRESENTATION: A 24-year-old Nepali female presented with a 3-week history of low-grade fever, headache, and painful, discrete, unilateral left-sided cervical and axillary lymphadenopathy. Among the multitude of tests that were carried out, Erythrocyte Sedimentation Rate was raised and there was thrombocytopenia while other tests were normal. Painful lymphadenopathy pointed to bacterial lymphadenitis while chronic low-grade fever suggested tuberculosis. A cervical lymph node was excised for histopathological examination to reach an accurate diagnosis. On the basis of pathognomonic features viz., paracortical foci composed of various types of histiocytes including crescentic type in the background of abundant apoptotic karyorrhectic debris, a diagnosis of Kikuchi–Fujimoto disease was made. On follow-up evaluation after 6 weeks, the patient had no systemic symptoms, enlarged lymph nodes had regressed in size significantly, and Erythrocyte Sedimentation Rate and platelet count had become normal. CONCLUSION: Kikuchi–Fujimoto disease should be kept in the differential diagnosis of lymphadenopathy in young patients, female or male even in tuberculosis-endemic countries and even in patients who have unusual features; for example thrombocytopenia and involvement of axillary lymph nodes in addition to cervical lymph nodes as in this case.